The Influence of Scarcity Perception and FOMO on Gen Z Impulse Buying in Cirebon City - Muhammad Yasin Abbas; Febry Ilham Pratama; Jefry Romdonny; Yono Maulana (Indonesian Interdisciplinary Journal of Sharia Economics)
Social media use and the quick expansion of e-commerce have altered Generation Z's spending habits, particularly by promoting impulsive purchases. The purpose of this research is to ascertain how Gen Z in Cirebon City impulsively purchases items in response to perceived scarcity and FOMO. The research methodology is survey-based and quantitative. Participants in this research were 231 respondents who are frequent Shopee e-commerce consumers in Cirebon City. The Partial Least Square-Structural Equation Modelling (PLS-SEM) approach was used to analyse the data using the SmartPLS 3 software. The findings demonstrated that impulsive purchase was positively and significantly impacted by both perceived scarcity and FOMO, partly and concurrently. With an R-squared value of 0.382, the two independent variables may account for 38.2% of the variable related to impulsive purchase. These findings support the Stimulus-Organism-Response and psychological reactance theories, which explain that external pressures, such as scarcity and social anxiety, can encourage unplanned buying behavior. This research provides implications for businesses to understand the importance of ethics in scarcity-based marketing strategies and the importance of digital financial literacy education among Gen Z to reduce irrational consumptive behavior.